APPLICATION HOW TO OVERCOME THE PROBLEM SKIN AND BEAUTY THROUGH TRADITIONAL TREATMENT USING VISUAL BASIC 6.0 PROGRAMMING LANGUAGE - Binsar David (Jurnal Manajemen Informatika, 2010)
Many of the problems experienced by the community, especially the problem ofdisease and, more particularly the problem of skin diseases. The problem isespecially needed an expert / expert in that field. Time, money, and laziness ofpeople to call an expert in addressing the issue. Therefore, the authors make anapplication of traditional medicine, and the more specific issues regarding skinproblems because the skin is a minor problem that society / people reluctant to seekexpert skin. Applications that used to use Visual Basic 6.0, the reason being that theresulting capacity is not too large, and because it greatly simplifies the visual shapeof the user.